Combined genetic and epigenetic alterations of the TERT promoter affect clinical and biological behavior of bladder cancer. Issue 7 (30th December 2018) - Leão, Ricardo; Lee, Donghyun; Figueiredo, Arnaldo; Hermanns, Thomas; Wild, Peter; Komosa, Martin; Lau, Irene; Mistry, Mathew; Nunes, Nuno Miguel; Price, Aryeh J.; Zhang, Cindy; Lipman, Tatiana; et al.
Abstract : In urothelial bladder cancer (UBC), risk stratification remains an important unmet need. Limitless self‐renewal, governed by TERT expression and telomerase activation, is crucial for cancer progression. Thus, telomerase activation through the interplay of mutations ( TERT p Mut ) and epigenetic alterations in the TERT promoter may provide further insight into UBC behavior. Here, we investigated the combined effect of TERT p Mut and the TERT Hypermethylated Oncological Region (THOR) status on telomerase activation and patient outcome in a UBC international cohort ( n = 237). We verified that TER Tp Mut were frequent (76.8%) and present in all stages and grades of UBC. Hypermethylation of THOR was associated with higher TERT expression and higher‐risk disease in nonmuscle invasive bladder cancers (NMIBC). TERT p Mut alone predicted disease recurrence (HR: 3.18, 95%CI 1.84 to 5.51, p < 0.0001) but not progression in NMIBC. Combined THOR high / TER Tp Mut increased the risk of disease recurrence (HR 5.12, p < 0.0001) and progression (HR 3.92, p = 0.025). Increased THOR hypermethylation doubled the risk of stage progression of both TERT p wt and TERT p Mut NMIBC. These results highlight that both mechanisms are common and coexist in bladder cancer and while TERT p Mut is an early event in bladder carcinogenesis THOR hypermethylation is a dynamic process that contributes to disease progression. While the absence of alterations comprises an extremely indolent phenotype, the combined genetic and epigenetic alterations of TERT bring additional prognostic value in NMIBC and provide a novel insight into telomere biology in cancer. Abstract : What's new? Telomerase reverse transcriptase ( TERT ) activation is central to cancer cell immortalization. It acts, however, through relatively unknown mechanisms. In urothelial bladder cancer (UBC) in particular, TERT activation can occur in the presence or absence of mutation, raising questions about alternative activation mechanisms. Our study shows that hypermethylation of the TERT promoter (THOR) plays a key part in UBC, being a dynamic and progressive process, with hypermethylation levels increasing with bladder cancer severity. Moreover, both hypermethylation and TERT promoter mutation contributed to increased telomerase expression. The findings provide insight into telomere biology in UBC and may be applicable to other tumors.